Belimumab in systemic lupus erythematosus (SLE): evidence-to-date and clinical usefulness. (March 2017) - Guerreiro Castro, Sara; Isenberg, David A.
Systemic lupus erythematosus (SLE) is a complex autoimmune rheumatic disease with multiple presentations, whose management presents many challenges. Many disease modifying or immunosuppressive drugs have been used with limited success, especially in patients with more severe disease activity. Belimumab is the first drug to be approved specifically for the treatment of SLE in more than 50 years. By blocking the B-cell activating factor, it interferes in B-cell differentiation and survival. Here we consider the results of the clinical trials that led to its approval, as well as the post-hoc analyses, follow-up studies and the current trials.